2021
DOI: 10.1038/s41568-021-00344-2
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in tumour immunity and therapy

Abstract: Autophagy is a regulated mechanism that removes unnecessary or dysfunctional cellular components and recycles metabolic substrates. In response to stress signals in the tumour microenvironment, the autophagy pathway is altered in tumour cells and immune cells -thereby differentially affecting tumour progression, immunity and therapy. In this Review, we summarize our current understanding of the immunologically associated roles and modes of action of the autophagy pathway in cancer progression and therapy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
196
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(220 citation statements)
references
References 213 publications
3
196
0
Order By: Relevance
“…Extracellular or intracellular pattern recognition receptors, including Toll-like receptors, together with advanced glycosylation end product-specific receptor, purinergic P2RX7 receptors and absent in melanoma 2, receive these signals and activate downstream signaling for calcium activation and the initiation of autophagy. Studies have shown that the E3 ligase TNF receptor-associated factor 6-mediated ubiquitination of Beclin 1 is critical for TLR4-triggered autophagy in macrophages, which releases Beclin 1 from its inhibitor BCL2 [108][109][110].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…Extracellular or intracellular pattern recognition receptors, including Toll-like receptors, together with advanced glycosylation end product-specific receptor, purinergic P2RX7 receptors and absent in melanoma 2, receive these signals and activate downstream signaling for calcium activation and the initiation of autophagy. Studies have shown that the E3 ligase TNF receptor-associated factor 6-mediated ubiquitination of Beclin 1 is critical for TLR4-triggered autophagy in macrophages, which releases Beclin 1 from its inhibitor BCL2 [108][109][110].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…Accumulating evidence has indicated that autophagy is involved in drug-mediated anticancer therapy ( 10 , 28 , 29 ); therefore, the present study investigated whether TCG induced autophagy in the SW480 cell line. First, LC3-II accumulation, a hallmark of autophagy, and the levels of Beclin 1 and Atg5, two autophagy-related proteins, were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is a conserved catabolic process whereby aggregated proteins or damaged organelles are sequestered by double-membrane autophagosomes and degraded in autolysosomes, which maintains cellular homeostasis under physiological conditions (9,10). Induction of autophagy has been observed in various types of cancer cells challenged with intra-and extracellular stresses; however, the role of autophagy in regulating the fate of cancer cells remains controversial (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In-depth evaluation of hydroxychloroquine, it revealed that it could be considered an effective autophagy inhibitor [ 144 ]. Autophagy is a self-degrading intracellular process involving tumor suppression and promotion [ 145 ]. However, inhibition of autophagy with hydroxychloroquine can not only hinder the autophagic protective effect but also increase dysfunctional mitochondria and ROS production, and a further study found that ROS was the main mechanism of enhanced cytotoxicity with autophagy inhibition [ 144 ].…”
Section: Repurposed Drug-regulated Ros Homeostasis As a Novel Cancer Therapeutics In Oncologymentioning
confidence: 99%